A Model for Lender-Borrower Trust in Peer-To-Peer Lending - Sukmaningsih, Dyah Wahyu (ComTech: Computer, Mathematics and Engineering Applications, 2018)
This research examined factors that influenced lender’s trust towards the borrower. The peerto-peer lending platform facilitated lending mechanism between lender and borrower. However, the loan was often considered as an unsecured loan, since there was a lack of traditional financial data. Using literature review, this research analyzed the determinant factor to establish trust between borrower and lender. Based on Elaboration Likelihood Model (ELM), the result of this research proposes a model for trust building between lender and borrower. The model categorizes information to establish trust into hard information, soft information, and social capital.